Preparation method and application of transition metal enhanced manganese-doped calcium phosphate class oxidase nanomaterial

CN122875263APending Publication Date: 2026-10-09ZHENGZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611070421.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-18
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0006]然而,上述报道均侧重于锰掺杂磷酸钙的医学应用、吸附或热稳定性,对其自身的纳米酶特性(特别是类氧化酶特性)几乎没有提及

Benefits of technology

[0020]1. 开创性地赋予磷酸钙以类氧化酶功能。首次发现并通过实验证实,锰掺杂磷酸钙在无过氧化氢条件下具有高效的类氧化酶活性,彻底改变了该材料仅作为类过氧化物酶的技术认知。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122875263A_ABST
    Figure CN122875263A_ABST
Patent Text Reader

Abstract

The application discloses a transition metal-enhanced manganese-doped calcium phosphate oxidase-like nanomaterial, a preparation method and application thereof, and belongs to the technical field of nanomaterials. The nanomaterial is a calcium phosphate with a hydroxyapatite crystal phase, and manganese ions are doped in the crystal lattice of the nanomaterial; preferably, the nanomaterial is also co-doped with nickel or cobalt. The preparation method comprises the following steps: mixing a phosphorus source with a calcium source and a manganese source, adjusting the pH to 10.0-12.0, and then separating, washing and drying the nanomaterial after hydrothermal reaction at 140-220 DEG C. The nanomaterial can catalyze the oxidation of 3,3',5,5'-tetramethylbenzidine (TMB) to produce a color reaction with dissolved oxygen as an electron acceptor without hydrogen peroxide, and the main active species is a superoxide anion free radical (·O2⁻). Experiments show that the co-doping of nickel or cobalt has a highly specific enhancement effect, and the oxidase-like activity can be increased by more than 2 times under the optimal doping amount (5%); and the doping of iron, copper and zinc has an obvious inhibitory effect. The material has a low cost and excellent biocompatibility, and has a wide application prospect in the fields of antibacterial materials and colorimetric sensing (such as detection of antioxidants like tea polyphenols).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of nanoenzyme materials technology, specifically relating to a manganese-doped calcium phosphate nanomaterial with oxidase-like activity and its preparation method, particularly to a method for significantly enhancing its oxidase-like activity through nickel or cobalt co-doping, and the application of this material in colorimetric sensing, antibacterial and other fields under hydrogen peroxide-free conditions. Background Technology

[0002] Nanozymes are a class of nanomaterials with enzyme-like catalytic activity. Among them, oxidase-like enzymes can directly catalyze the oxidation of substrates (such as 3,3',5,5'-tetramethylbenzidine, TMB) with dissolved oxygen to produce color signals in the absence of hydrogen peroxide, which has unique advantages in constructing simple and stable biosensors and novel antibacterial materials.

[0003] In the prior art, Han et al. synthesized manganese-doped calcium tungstate (CaWO4:Mn) as an oxidase-like enzyme. x Mn 1-x WO4 (with high oxidase-like activity to detect antioxidants) is used, but tungsten is expensive, and the biocompatibility of calcium tungstate needs further investigation. In contrast, calcium phosphate (especially hydroxyapatite) has excellent biocompatibility, low cost, and good chemical stability.

[0004] Currently, research on manganese-doped calcium phosphate mainly focuses on medical treatment and applications. For example, Xia et al. used it for bone regeneration and dental disease treatment (Manganese enhances the osteogenic effect of silicon-hydroxyapatite nanowires by targeting T lymphocyte polarization); Feng et al. studied its biodegradability for targeted drug delivery (Urinary microenvironment-degradable nanocapsules for traceable therapy of diabetic nephropathy); in addition, Fu et al. studied the application of Mn elemental properties in chemokinetics (Biodegradable manganese-doped calcium phosphate nanotheranostics for traceable cascade reaction-enhanced anti-tumor therapy), and Cai et al. used it for sonodynamic immunotherapy (Biodegradable and piezoelectric Mn-doped hydroxyapatite for sonodynamic immunotherapy).

[0005] Besides medical applications, some studies have focused on the adsorption and high-temperature phase transition properties of manganese-doped calcium phosphate. For example, Wu et al. disclosed a precipitation method for preparing manganese-doped hydroxyapatite for the adsorption of heavy metal ions (CN114870792A); Zhu et al. prepared trivalent manganese ion-doped hydroxyapatite through high-temperature treatment to enhance antibacterial and osteogenic properties (CN112062114A); and Chen et al. studied the hierarchical structure construction and catalytic performance of manganese-doped calcium phosphate nanoclusters (Manganese-doped calcium phosphate nanoclusters with hierarchical structure: construction and performance).

[0006] However, the aforementioned reports all focus on the medical applications, adsorption, or thermal stability of manganese-doped calcium phosphate, with almost no mention of its own nanoenzyme properties (especially oxidase-like properties). To date, no literature or patent has disclosed a technical solution where manganese-doped calcium phosphate itself possesses oxidase-like activity. Summary of the Invention

[0007] The purpose of this invention is to overcome the shortcomings of the prior art and provide a novel manganese-doped calcium phosphate nanomaterial that can exert oxidase-like functions without hydrogen peroxide. Through the synergistic regulation of specific hydrothermal conditions and the manganese doping ratio, this invention unexpectedly activated oxidase-like activity in this material system. Furthermore, it was discovered that appropriate co-doping with only nickel and cobalt can enhance this activity several times over, while doping with common transition metals such as iron, copper, and zinc strongly inhibits the activity. This highly specific ionic effect could not have been predicted from existing knowledge.

[0008] The technical solution of the present invention is as follows:

[0009] A manganese-doped calcium phosphate oxidase nanomaterial is characterized in that the material is calcium phosphate in the hydroxyapatite crystal phase, and manganese ions are doped in its crystal lattice; the material can directly use dissolved oxygen as an electron acceptor to catalyze the oxidation of TMB substrate to produce a blue product under conditions without hydrogen peroxide, exhibiting oxidase-like activity.

[0010] The preparation method of the material includes the following steps:

[0011] (1) Dissolve the phosphorus source in water to obtain solution A, and dissolve the calcium source and manganese source in water in a certain proportion to obtain solution B;

[0012] (2) Add solution B to solution A while stirring, and adjust the pH to 10.0-12.0 with alkaline solution to form a precursor suspension;

[0013] (3) Transfer the precursor suspension into the reactor and hydrothermally react at 140-220°C for 6-20 hours;

[0014] (4) After the reaction is complete, the solid product is separated, washed and dried to obtain the nanomaterial.

[0015] Preferably, the molar ratio of manganese doping is 9.1% to 37.5% (i.e., the Ca:Mn molar ratio is 5:0.5 to 5:3), with the optimal ratio being 16.7% (Ca:Mn = 5:1), at which the oxidase-like activity is the highest.

[0016] Preferably, the hydrothermal temperature is 200°C, at which temperature a hydroxyapatite crystal phase with high crystallinity and suitable defect states can be obtained, enabling the material to exhibit optimal oxidase-like activity.

[0017] As a key improvement of the present invention, a nickel source or a cobalt source may be added to solution B in step (1) above to achieve co-doping of nickel or cobalt. Preferably, the amount of nickel or cobalt doping is 0.5% to 10% of the molar amount of the metal atoms and manganese, and more preferably 5%. Under these preferred conditions, nickel co-doping can refine the material particles to 10 to 20 nm, significantly increase the surface adsorbed oxygen content, and multiply the activity of oxidase-like enzymes.

[0018] It is particularly important to note that not all transition metals produce an enhancing effect. Through extensive experiments, the inventors discovered that in this system, the doping of iron, copper, and zinc actually leads to a decrease in oxidase-like activity, exhibiting a clear metal ion selectivity—a completely unexpected technical effect.

[0019] The present invention has the following beneficial effects:

[0020] 1. Innovatively endowing calcium phosphate with oxidase-like function. For the first time, manganese-doped calcium phosphate was discovered and experimentally demonstrated to possess highly efficient oxidase-like activity under hydrogen peroxide-free conditions, completely changing the technical understanding of this material as merely a peroxidase-like substance.

[0021] 2. The source of activity is clearly defined, and the mechanism is well understood. Through reactive oxygen species capture experiments and dissolved oxygen dependence experiments, it was confirmed that the main active species of the oxidase-like activity of this material is superoxide anion radical (·O2⁻), and the catalytic process is strictly dependent on dissolved oxygen, providing solid mechanistic support for the oxidase-like properties.

[0022] 3. Discovery of a specific enhancement effect from Ni / Co co-doping. Co-doping with only nickel and cobalt significantly enhances the activity of oxidase-like enzymes (more than doubling under optimal conditions), while common transition metals such as iron, copper, and zinc invariably inhibit activity. This highly selective synergistic effect is a first discovery in calcium phosphate-based nanozymes, demonstrating outstanding inventiveness.

[0023] 4. The preparation method is green and controllable. The material structure and properties can be precisely controlled simply by adjusting the hydrothermal temperature and the raw material ratio. The process is simple, easy to scale up, and the raw materials used are inexpensive, readily available, and have excellent biocompatibility. Attached Figure Description

[0024] Figure 1 XRD patterns (a) CMP-1 sample; (b) 5Ni-CMP-1 sample; (Preparation conditions: hydrothermal temperature 200℃, hydrothermal time 10 hours)

[0025] Figure 2 SEM images (ac) CMP-1 samples at different magnifications; (d) Energy dispersive spectroscopy (EDS) of CMP-1 samples (preparation conditions: hydrothermal temperature 200℃, hydrothermal time 10 hours).

[0026] Figure 3 SEM images (ac) of 5Ni-CMP-1 samples at different magnifications; (d) Energy dispersive spectroscopy (EDS) of 5Ni-CMP-1 samples (preparation conditions: hydrothermal temperature 200℃, hydrothermal time 10 hours).

[0027] Figure 4 XPS full spectrum (a) CMP-1 sample; (b) 5Ni-CMP-1 sample; (all prepared under hydrothermal conditions of 200℃ and 10 hours)

[0028] Figure 5 XPS spectra: (a) Mn 2p spectrum; (b) Mn 3s spectrum; (c) O 1s spectrum; (Upper CMP-1 sample, lower 5Ni-CMP-1 sample, both prepared under hydrothermal conditions of 200℃ and 10 hours)

[0029] Figure 6 The UV-Vis spectra of different systems were obtained using TMB as the colorimetric reagent. (a) Samples with different calcium-manganese ratios (hydrothermal temperature 200℃, hydrothermal time 10 hours); (b) Samples with different hydrothermal temperatures (calcium-manganese ratio fixed at 5:1, hydrothermal time 10 hours).

[0030] Figure 7 The UV-Vis spectra of different systems were obtained using TMB as the colorimetric agent. (a) Different Ni doping ratios; (b) Different Fe doping ratios; (calcium-manganese ratio 5:1, preparation conditions were all hydrothermal temperature 200℃, hydrothermal time 10 hours)

[0031] Figure 8 (a) UV-Vis spectra of TMB alone, 5Ni-CMP-1 sample, TMB+5Ni-CMP-1 sample, and TMB+5Ni-CMP-1 sample after nitrogen purging; (b) 1 blank control sample, 2-addition of p-benzoquinone quencher, 3-addition of isopropanol, 4-addition of EDTA-2Na, 5-addition of histidine (using 5Ni-CMP-1 sample, preparation conditions: hydrothermal temperature 200℃, hydrothermal time 10 hours).

[0032] Figure 9 Steady-state kinetic curves of CMP-1: (a) Michaelis curve, (b) double reciprocal curve; (CMP-1 preparation conditions: hydrothermal temperature 200℃, hydrothermal time 10 hours)

[0033] Figure 10 CMP-1 detection of tea polyphenols: (a) UV-Vis spectra of the system at different tea polyphenol concentrations, (b) linear relationship curve between tea polyphenol concentration and the peak value of the system at 652 nm (CMP-1 preparation conditions: hydrothermal temperature 200℃, hydrothermal time 10 hours). Detailed Implementation

[0034] The present invention will be further described in detail below through specific embodiments, but the content of the present invention is not limited thereto.

[0035] Preparation Example 1: Nanomaterials with different manganese doping ratios

[0036] Solution A was prepared by dissolving 0.82 g of Na3PO4 in 15 mL of deionized water. Solution B was prepared by dissolving 0.83 g of CaCl2 and the corresponding mass of MnCl2·4H2O in 15 mL of deionized water, with Ca:Mn molar ratios of 1:0, 5:0.5, 5:1, 5:2, 5:3, and 0:1, corresponding to Mn molar ratios of 0%, 9.1%, 16.7%, 28.6%, 37.5%, and 100%, respectively. Solution B was poured into solution A with stirring, and after stirring for 15 minutes, the pH was adjusted to 10.0 with 1 mol / L NaOH solution. The resulting suspensions were transferred to a 100 mL polytetrafluoroethylene-lined reactor and reacted at 200°C for 10 hours. After natural cooling, the precipitate was collected by centrifugation, washed three times with deionized water, and dried at 60°C for 6 hours to obtain samples with different manganese doping ratios, which were named CPO (pure calcium phosphate), CMP-0.5 (Ca:Mn = 5:0.5), CMP-1 (Ca:Mn = 5:1), CMP-2 (Ca:Mn = 5:2), CMP-2 (Ca:Mn = 5:3), and MPO (pure manganese phosphate).

[0037] like Figure 1 As shown in the XRD pattern in section a, the product CMP-1 at 200℃ is a pure hydroxyapatite crystalline phase with high crystallinity. Figure 2 As shown in the SEM image, CMP-1 has a rice-grain-like nanostructure with a size of approximately 100 nm × 10 nm. Figure 2 The energy spectrum in d shows that CMP-1 contains Ca, Mn, O and P elements, and the elements are evenly distributed in CMP-1.

[0038] Preparation Example 2: CMP-1 at different hydrothermal temperatures

[0039] With the Ca:Mn molar ratio fixed at 5:1, a series of samples were obtained by changing the hydrothermal temperature to 140℃, 160℃, 180℃, 200℃ and 220℃, following the method of preparation example 1.

[0040] Preparation Example 3: Transition Metal Co-doped CMP-1

[0041] With a fixed Ca:Mn molar ratio of 5:1, when preparing solution B, additional amounts of NiCl2·6H2O, CoCl2·6H2O, FeCl3·6H2O, CuCl2·2H2O, or ZnCl2 were added to make the percentages of doped metal (M) to Mn molar amounts 0.5%, 2%, 5%, and 10%, respectively. Subsequently, following the method in Example 1, a hydrothermal reaction was carried out at 200°C for 10 hours, and the resulting sample was named xM-CMP-1 (x represents the doping percentage, and M represents the doped metal).

[0042] like Figure 1 As shown in the XRD pattern in b, 5Ni-CMP-1 is a hydroxyapatite crystalline phase, but its crystallinity is very weak. Figure 3 As shown in the SEM image, 5Ni-CMP-1 consists of irregular nanoparticles with a size of approximately 10 nm to 20 nm. Figure 3 The energy spectrum of d shows that CMP-1 contains Ca, Mn, O, P and Ni elements, and each element is evenly distributed in 5Ni-CMP-1.

[0043] Test Example 1: Oxidase-like Activity and Influencing Factors

[0044] Each sample was ultrasonically dispersed in acetate buffer (pH 5.0) to prepare a 1 mg / mL dispersion. 10 μL of sample solution, 180 μL of buffer solution, and 10 μL of TMB solution (10 mmol / L) were added sequentially to a 96-well plate. After thorough mixing, the absorbance at 652 nm was monitored over time at room temperature in an air-saturated environment free of hydrogen peroxide.

[0045] like Figure 6 The results showed that neither CPO nor MPO exhibited oxidase-like activity. CMP-0.5, CMP-1, and CMP-2 all showed activity, with CMP-1 (Ca:Mn = 5:1) showing the highest activity, indicating that the manganese doping amount needs to be controlled within an appropriate range to effectively activate the crystal lattice.

[0046] Hydrothermal temperature also affects the activity of oxidase-like enzymes in the samples. For example... Figure 6 As shown in b, CMP-1 prepared at 200℃ showed the best activity, followed by that prepared at 180℃. The activity of samples prepared at 160℃ and 220℃ decreased significantly, and the activity of samples prepared at 140℃ was very low.

[0047] After co-doping with transition metals, nickel and cobalt doping significantly enhance activity. For example... Figure 7 As shown in figure a, the activity of 5Ni-CMP-1 is approximately 2.5 times that of undoped CMP-1. The activity initially increases and then decreases with increasing Ni doping concentration, with 5% showing the optimal activity. In stark contrast, the oxidase-like activities of all iron, copper, and zinc-doped samples are significantly lower than those of CMP-1. Figure 7 As shown in b, after iron doping, the activity of 2Fe-CMP-1 is only 50% of that of CMP-1. This high selectivity, which only has a positive response to Ni / Co, cannot be deduced from existing knowledge.

[0048] Test Example 2: Verification of Oxidase-like Mechanism

[0049] To confirm the nature of the catalytic process, dissolved oxygen control experiments and reactive oxygen capture experiments were conducted using 5Ni-CMP-1 as the subject.

[0050] In the dissolved oxygen control experiment, the buffer solution was pre-purified with high-purity nitrogen for 30 minutes to completely remove oxygen, and the TMB colorimetric reaction was carried out under sealed conditions. Figure 8 b shows that the absorbance of the deoxygenated system is only about 30% of that of the air-saturated system. This directly confirms that the catalytic process is strictly dependent on the participation of dissolved oxygen, which is consistent with the catalytic characteristics of oxidases.

[0051] In reactive oxygen species (ROS) capture experiments, different scavenging agents were added to the standard TMB colorimetric system: isopropanol (·OH scavenger), EDTA-2Na (hole scavenger), p-benzoquinone (·O2⁻ scavenger), and L-histidine (¹O2 scavenger). For example... Figure 8 As shown in b, the addition of p-benzoquinone suppressed the color development of the system by approximately 85%, while the suppression effects of other scavenging agents were all less than 15%. This fully demonstrates that the superoxide anion radicals (·O2⁻) generated by the material catalysis are the main active species.

[0052] Mechanism Investigation Example 1: Mechanism Investigation of Ni Doping to Enhance Activity

[0053] To further elucidate the underlying reasons for the enhanced activity of nickel-doped oxidases, this invention presents a systematic comparative analysis of the morphology and surface electronic states of the optimal sample (5Ni-CMP-1) and the undoped sample (CMP-1).

[0054] As shown in the scanning electron microscope (SEM) images, undoped CMP-1 exhibits a distinct micron-sized particle aggregation morphology. Figure 2 a), while the grain size of 5Ni-CMP-1 is significantly refined, the distribution is more uniform, and the average grain size is reduced to 10~20 nm (a). Figure 3 a) The sharp reduction in grain size leads to a significant increase in the specific surface area of ​​the material, thereby exposing more manganese active sites, which is the morphological basis for the enhanced activity of oxidase-like enzymes.

[0055] X-ray photoelectron spectroscopy (XPS) full spectrum ( Figure 4 This confirms the successful doping of Ni without the introduction of other impurity elements.

[0056] Further high-resolution peak fitting was performed on Mn 2p, Mn 3s, and O 1s. Compared with CMP-1, after Ni doping, the Mn 2p peak tends to shift towards the direction of higher binding energy. Figure 5 a) indicates that the valence state of Mn ions tends to increase. For example... Figure 5 As shown in b, comparing the Mn 3s spectra of CMP-1 and 5Ni-CMP-1 reveals that after Ni doping, the Mn 3s multiple splitting energy (ΔE) decreases from 6.1 eV to 5.9 eV, also indicating that the average valence state of Mn ions has increased. Higher valence manganese ions are more conducive to promoting the migration of lattice oxygen and enhancing the adsorption capacity for dissolved oxygen.

[0057] From the O 1s spectrum ( Figure 5 c) It can be seen that after Ni doping, the oxygen at 533.5 eV belongs to surface adsorbed oxygen / defect oxygen (O). v The peak area ratio of ) increases significantly. The increase in surface-adsorbed oxygen indicates that the material surface has abundant oxygen vacancies and active oxygen species, which directly facilitates the reduction of dissolved oxygen to superoxide anion radicals (·O₂⁻) on the material surface. Furthermore, after Ni doping, the lattice oxygen O L The proportion decreased significantly, which is consistent with the results of XRD and SEM, indicating that Ni has a poisoning effect on CMP, destroying its lattice, causing a decrease in the crystallinity of the material, a reduction in particle size, and an increase in the specific surface area of ​​the material, which to some extent is the reason for its increased enzyme-like activity.

[0058] In summary, the enhancement of CMP-type oxidase activity by Ni doping is not due to physical mixing, but rather a synergistic effect of morphology refinement and electronic state reconstruction. The introduction of Ni²⁺ / Ni³⁺ inhibits excessive grain growth and increases specific surface area; on the other hand, it adjusts the coordination environment and valence state of Mn, significantly increasing the content of adsorbed oxygen / oxygen vacancies on the surface, thereby greatly improving the catalytic efficiency of electron capture and conversion of dissolved oxygen in aqueous solution into ·O₂⁻. This mechanism is consistent with the experimental results in Example 2 where ·O₂⁻ was the main active species.

[0059] Test Example 3: Steady-state dynamics analysis

[0060] like Figure 9 As shown, with the concentration of CMP-1 fixed, the initial reaction rate was measured at different TMB concentrations. The Michaelis constant K was obtained by fitting the Michaelis equation. m (0.38 mM) and maximum reaction rate V max (3.33*10) -7 Ms -1 ).

[0061] Test Example 4: Application Case—Colorimetric Detection of Glutathione

[0062] By utilizing the oxidase-like activity of CMP-1, a colorimetric sensing method for reduced biothiols can be established. For example... Figure 10 As shown, in the TMB-5Ni-CMP-1 colorimetric system, the addition of different concentrations of tea polyphenols (TP) inhibited the oxidation and color development of TMB due to the competitive consumption of ·O₂⁻ by TP. The absorbance at 652 nm showed a good linear relationship with the TP concentration in the range of 0.25–2 mg / mL. Even with 5 times the concentration of interfering substances such as K⁺, Na⁺, glucose, and glycine in the system, the signal fluctuation was less than 5%, demonstrating excellent selectivity.

[0063] Test Example 5: Antibacterial Application

[0064] Without any added oxidant, the 5Ni-CMP-1 dispersion was mixed with Escherichia coli (approximately 10 μL). 6 Co-incubation with nickel (CFU / mL) was performed. After 20 minutes, plate counting results showed that the bacterial survival rate dropped to below 0.1%, achieving a sterilization rate of 99.9%. This highly efficient antibacterial activity stems from the large amount of ·O2⁻ generated on the surface of the material after nickel doping, which causes irreversible oxidative damage to bacteria.

Claims

1. A manganese-doped calcium phosphate oxidase nanomaterial, characterized in that, The nanomaterial is a hydroxyapatite crystal phase, and its lattice is doped with manganese ions. Under conditions where hydrogen peroxide is absent, the nanomaterial can use dissolved oxygen as an electron acceptor to catalyze the oxidation of the 3,3',5,5'-tetramethylbenzidine (TMB) substrate to produce a colorimetric result.

2. The nanomaterial according to claim 1, characterized in that, The molar amount of manganese doping, calculated as Mn / (Ca+Mn), is 9.1% to 37.5%, preferably 16.7%.

3. The nanomaterial according to claim 1, characterized in that, The nanomaterial is also co-doped with nickel or cobalt, wherein the molar amount of nickel or cobalt is 0.5% to 10% of the molar amount of manganese, preferably 5%.

4. The nanomaterial according to claim 3, characterized in that, The co-doped metal is either nickel or cobalt.

5. A method for preparing the nanomaterial as described in claim 1, comprising the following steps: (1) Dissolve the phosphorus source in water to obtain solution A, and dissolve the calcium and manganese sources in water to obtain solution B; (2) Mix solution B with solution A and adjust the pH to 10.0–12.0; (3) Transfer the mixture into the reactor and hydrothermally react at 140~220℃ for 6~20 hours; (4) Separate the solid product, wash and dry it to obtain the final product.

6. The method according to claim 5, characterized in that, Solution B in step (1) also contains a nickel source or a cobalt source to obtain nickel or cobalt co-doped nanomaterials.

7. The use of the nanomaterials according to any one of claims 1 to 4 in the preparation of colorimetric sensing reagents, antibacterial materials or organic pollutant degrading agents for non-disease diagnostic purposes.

8. The application according to claim 7, characterized in that, The colorimetric sensing reagent is used to detect antioxidants such as tea polyphenols and ascorbic acid, as well as reducing biomolecules such as glutathione, cysteine, dopamine, and glucose.

Citation Information

Patent Citations

  • Trivalent manganese ion doped hydroxyapatite material as well as preparation method and application thereof

    CN112062114A

  • Manganese-doped hydroxyapatite material as well as preparation method and application thereof

    CN114870792A